A General Framework for Performance Management Systems: Structure, Design, and Analysis. Issue 2 (21st February 2013) - Clardy, Alan
Abstract Employees may spend their time on the job behaving in a variety of ways. The purpose of a well‐designed performance management system should be to channel and motivate employees to concentrate their energies on value‐added performance. The extent to which an organization achieves this outcome depends upon the design and structure of its performance management system. The basic framework of any performance management system as presented here involves four levels of operations, policies, and practices: (1) executive leadership; (2) the infrastructure of strategy, measurement and control, and work process; (3) human resource policies and practices in attracting, hiring, developing, and compensating employees; and (4) workplace working conditions shaped and driven by the practices of managers and supervisors and the dynamics of the work group or team. The issues that performance improvement specialists need to consider in analyzing an organization's performance management system are noted.